PtMIr (M= Ni, Co, Fe, Mn, V, Ti) nanowires electrocatalysts towards ORR in acidic media - Wang, Qiang; Li, Chuang; Li, Guangwei; Li, Xiao; Luo, Sai; Han, Zhijia; Xing, Danmin; Liang, Changhai (Chemical engineering science, 2025)
[Display omitted] •Novel ternary PtMIr (M=Ni,Co,Fe,Mn,V,Ti) ultrathin nanowires synthesized via solvothermal method.•PtNiIr NWs exhibit superior ORR activity and stability over commercial catalysts.•Ir doping level optimization enhances catalytic performance of PtNiIr NWs/C.•1D anisotropic structure and Ir incorporation improve durability and activity. Developing high-performance and long-lasting electrocatalysts towards oxygen reduction reaction (ORR) remains a critical endeavor for advancements in fuel cell technology. In this work, we successfully synthesized a series of ternary ultrathin PtMIr (M = Ni, Co, Fe, Mn, V, Ti) nanowires (NWs), the ultrathin PtMIr NWs exhibit improved electrocatalytic performance for ORR. Within the series multimetallic NWs, the PtNiIr NWs showcase the most superior activity and stability toward ORR compared to other catalysts. Meanwhile, the effects of Ir doping content on ORR were investigated, the Pt86Ni10Ir4 NWs/C displayed mass activity (MA) of 1.58 A mg−1 and specific activity (SA) of 1.77 mA cm−2 for ORR, which are 10.83 and 9.94 times higher than those of the commercial Pt/C. Strikingly, the Pt86Ni10Ir4 NWs/C catalyst showed an impressive durability, with only a 4.9 % decrease in SA after undergoing 30,000 cycles of durability test. Comprehensive X-ray photoelectron spectroscopy (XPS) analyses have elucidated that the presence ofIr optimizes the electronic structure of nanocrystals, and electron transfer between atoms optimizes electronic structure, which may contribute to the improved catalytic properties.